Kemampuan Bacillus thuringiensis untuk Mengendalikan Spodoptera frugiperda J.E. Smith - Raden Jani; Samharinto Soedijo; Elly Liestiany (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Spodoptera frugiperda is the main pest that attacks corn plants, so it is necessary to control it. One of the control alternatives is using the biological agent Bacillus thuringiensis (Bt). In this study the use of biological agents B. thuringiensis bacteria against S. frugiperda larvae. This study aims to determine the ability of B. thuringiensis bacteria to control S. frugiperda on a laboratory scale. This study used a completely randomized design (CRD) with 4 treatments and 6 replications. The treatment used doses of 2 ml, 2.5 ml and 3 ml of B. thuringiensis bacteria and as a comparison, namely sterile water which acted as a control in this study. Mortality observations were made every 12 hours for 96 hours. Each replicate was infested with 10 S. frugiperda larvae so that 240 S. frugiperda larvae were obtained in each experimental unit. The results of this study indicate that the biological agent of B. thuringiensis at a dose of 3 ml has the pathogenicity ability to S. frugiperda mortality with a percentage of 23.3% and has the best lethal time value of 9.3 days to kill 50% of S. frugiperda.